2006
DOI: 10.1038/emm.2006.71
|View full text |Cite
|
Sign up to set email alerts
|

Berberine reduces the expression of adipogenic enzymes and inflammatory molecules of 3T3-L1 adipocyte

Abstract: Berberine (BBR), an isoquinoline alkaloid, has a wide range of pharmacological effects, yet its exact mechanism is unknown. In order to understand the anti-adipogenic effect of BBR, we studied the change of expression of several adipogenic enzymes of 3T3-L1 cells by BBR treatment. First, we measured the change of leptin and glycerol in the medium of 3T3-L1 cells treated with 1 µM, 5 µM and 10 µM concentrations of BBR. We also measured the changes of adipogenic and lipolytic factors of 3T3-L1. In 3T3-L1 cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(95 citation statements)
references
References 21 publications
6
86
0
1
Order By: Relevance
“…Reductions of plasma TAG by BBR were also observed in other studies in rats with diabetes and nephritis [42,43,47]. Results from several in vitro studies have demonstrated that BBR decreases TAG levels through regulating fatty acid metabolism toward the downregulation of adipogenesis [51][52][53]. BBR upregulates the phosphorylation of the AMPactivated protein kinase (AMPK), which phosphorylates and inactivates acetyl-CoA carboxylase (ACC) [51,52].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Reductions of plasma TAG by BBR were also observed in other studies in rats with diabetes and nephritis [42,43,47]. Results from several in vitro studies have demonstrated that BBR decreases TAG levels through regulating fatty acid metabolism toward the downregulation of adipogenesis [51][52][53]. BBR upregulates the phosphorylation of the AMPactivated protein kinase (AMPK), which phosphorylates and inactivates acetyl-CoA carboxylase (ACC) [51,52].…”
Section: Discussionmentioning
confidence: 61%
“…The inactivation of ACC results in the inhibition of fatty acid synthesis but the enhancement of fatty acid oxidation. In addition, BBR downregulates the expression of adipogenic enzymes and transcription factors [53]. These effects collectively lead to the inhibition of TAG synthesis and consequently the reduction of plasma TAG levels.…”
Section: Discussionmentioning
confidence: 99%
“…To answer the question whether BBR could affect the expression of proinflammatory genes in the WAT of obese animals, we first examined the adipogenic/lipogenic gene expression in the WAT of obese db/db mice. As we and others have shown (9,23,33), BBR decreased expression of most adipogenic/lipogenic genes such as aP2, peroxisome proliferator-activated receptor-␥, acetyl-CoA carboxylase, and fatty acid synthase in the WAT of obese db/db mice (Supplemental Fig. 1; supplemental data for this article are available online at the Am J Physiol Endocrinol Metab website).…”
Section: Bbr Suppresses the Expression Of Proinflammatory Genes In Thmentioning
confidence: 99%
“…Recent studies have demonstrated that the beneficial effects of BBR on metabolic disorders including weightreducing, cholesterol-lowering, anti-lipogenic, and hypoglycemic effects (23,28,33,54) are associated with activation of AMP-activated protein kinase (AMPK) in peripheral tissues (3,7,33). Additionally, it has been also reported that BBR suppresses the expression of inflammatory molecules in several cell types (9,22,27,29,32). However, it is unclear how BBR mediates anti-inflammatory responses, especially in macrophages.…”
mentioning
confidence: 99%
“…The anti-inflammatory effects of BBR have been observed in a variety of human and animal tissues, including the liver [35], adipose tissue [36], vascular endothelial cells [37], and intestine [38]. Although the detailed mechanisms remain to be determined, BBR was shown to reduce the levels of expression of genes encoding pro-inflammatory cytokines, including tumor necrosis factor-α (TNF-α), interleukins (ILs), prostaglandins (PGs), cyclooxygenase-2 (COX-2), and inducible nitric oxide synthase (iNOS), in an AMPactivated protein kinase (AMPK)-dependent manner [39].…”
Section: Inflammatory Diseasesmentioning
confidence: 99%